THE ASSESSMENT OF THE UKRAINIAN BANKING SECTOR᾿S FINANCIAL SOUNDNESS BY Z-INDEX - Гірна, Олександра (Socio-economic relations in the digital society, 2019)
Z-score is one of the most popular indicators of banks' soundness in the modern scientifi c literature. The paper analyzes the dynamics of the financial stability of the banking sector in Ukraine using the time-series of aggregated and weighted Z-scores during 2010—2017. Th e ROA dynamics as an element of Z-score was highlighted. Our empirical results are supportive of the measure, which uses rolling mean and standard deviation (or rolling median and range-based volatility) of ROA over previous sixteen quartiles, combined with the current period value of the equity-to-asset ratio. The paper reveals the efficiency of using the medianas a measure of the central tendency and range as a measure of variability for the Z-scores calculation in the case of Ukrainian banks. The weighted Z-index of the banking system when market shares of banks are selected as weighting factors could not assess the probability of insolvency. However, we propose to use it as an assessment of the cumulative effect of banks' fi nancial soundness, which might change through the time under the infl uence of internal and external transformations. The comparison of the market shares weighted Z-score with other indicators of the banking system stability confi rmedit’s using as an aggregated indicator of the banking system stability. The both aggregated and weighted Z-scores showed that the fi nancial stability of the Ukrainian banking system had reached a critical level.Group analysis points on the fi nancial soundness reduction primarily of the state banks from 2014 and confi rms the negative impact of the state monopolization in the banking sector. Low indicators of financial soundness of the banks with foreign capital may indicate a low interest of foreign investors in putting money in the banking business in Ukraine undercurrent conditions. Th e best among three investigated groups were indicators of financial soundness of banks with Ukrainian capital, which retained their presence on the market after cleaning of the banking systemin 2015—2017 and showed stabilization of their activities.
Keywords: banking sector; financial soundness; insolvency risk; Z-score